Convenient One-Pot Three-Component Synthesis of Trifluoromethylated Tetrahydrobenzo[g]chromene Derivatives - Duan, Yijun; Wang, Xu; Xu, Xiaoling; Kang, Zhangping; Zhang, Min; Song, Liping; Deng, Hongmei (Synthesis, 2013)
A series of ethyl 4-(het)aryl-5,10-dioxo-2-hydroxy-2-(trifluoromethyl)-3,4,5,10-tetrahydro-2H-benzo[g]chromene-3-carboxylates were efficiently synthesized from 2-hydroxynaphthoquinone, aromatic aldehydes, and ethyl 4,4,4-trifluoro-3-oxobutanoate by a one-pot multicomponent reaction catalyzed by the combination of ammonium acetate and acetic acid. The benzochromenes are presumably formed through an initial Knoevenagel condensation followed by a Michael addition and regioselective intramolecular annulation. The dehydration reaction of the hemiketal moiety to the corresponding dehydrated product was also studied.
Keywords: multicomponent reactions; quinones; aldehydes; cyclizations; heterocycles; catalysis; fluorine; fused-ring systems